2007
DOI: 10.1152/ajpregu.00745.2006
|View full text |Cite
|
Sign up to set email alerts
|

Low fat adiponectin expression is associated with oxidative stress in nondiabetic humans with chronic kidney disease—impact on plasma adiponectin concentration

Abstract: In spite of association between high plasma adiponectin and high metabolic and cardiovascular (CV) risk, highest adiponectin increments retain CV and metabolic protective effects in advanced chronic kidney disease (CKD). Passive accumulation can favor CKD-associated hyperadiponectinemia but potential additional regulation by adipose tissue remains undefined. Oxidative stress (OS) is associated with metabolic and CV disease and with CKD [increasing from conservative treatment (CT) to maintenance hemodialysis (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Systemic inflammation is common in CKD24,30 and was activated in the current model as indicated by proinflammatory changes in circulating cytokines 16. Ghrelin treatment resulted in lower plasma concentrations of proinflammatory cytokines,16 consistent with reported in vitro anti-inflammatory ghrelin effects 31.…”
Section: Discussionsupporting
confidence: 81%
“…Systemic inflammation is common in CKD24,30 and was activated in the current model as indicated by proinflammatory changes in circulating cytokines 16. Ghrelin treatment resulted in lower plasma concentrations of proinflammatory cytokines,16 consistent with reported in vitro anti-inflammatory ghrelin effects 31.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results have been shown in other studies. 45,46 The present results indicate that the increased OS in obese individuals can be explained by the decreased adiponectin level that may lead to deficiency of the protective HDL-C. As it was found that there is a strong inverse association between adiponectin and fractional catabolic rate of ApoA-1 which is a major structural apolipoprotein of HDL-C. 47 Deficiency of HDL-C in obese individuals was associated with elevated levels of oxidative stress and impairment of its antioxidant effects. 48 In this work, albuminuria was positively correlated with TBARs and negatively correlated with adiponectin.…”
Section: Discussionsupporting
confidence: 49%
“…In the general population, systemic clinical hypoadiponectinemia is closely associated with obesity, type 2 diabetes, and coronary artery disease, and the increased oxidative stress in adipose tissue that accumulates in obesity associates with decreased adiponectin production (36). In CKD patients, reduction in oxidative stress through blockade of the angiotensin II type 1 receptor ameliorates adiponectin concentration (37), and oxidative stress is an important determinant of low fat adiponectin expression (38). A similar oxidative stress-related mechanism might also, at least in part, affect PTX3 production in adipocytes.…”
Section: Discussionmentioning
confidence: 99%